Reliability and validation of the Thai version of the Cumberland Ankle Instability Tool (CAIT-THA) - Yingyongsaksri S. (2023)
Purpose: This study aimed to provide a version of Cumberland Ankle Instability Tool (CAIT) for the Thai younger adult population and examine psychometric properties and determine the cut-off score. Methods: CAIT-Youth Thai version was modified to CAIT Thai version (CAIT-THA). To validate the CAIT-THA psychometric properties, 72 with chronic ankle instability (CAI) and 72 without (age 23.45 ± 4.45 years) were recruited. The validation was carried out by using internal consistency (Cronbach’s alpha), concurrent validity (Spearman’s rank correlation coefficient), discriminative validity (Receiver Operating Characteristic (ROC) curve), and test-retest reliability (intraclass correlation coefficient; ICC). A cut-off score was determined via Youden’s index. Results: Validation showed good internal consistency (Cronbach’s alpha = 0.837), and concurrent validity (Spearman’s rank correlation coefficient = 0.762 and 0.731 for right ankle and left ankle, respectively). Test-retest reliability was excellent with ICC (2,1) of 0.945 (95% CI = 0.93–0.96). A cut-off score of ≤ 25, determined by ROC curve and Youden’s index, was distinguished between participants with and without CAI. CAIT-THA obtained 97.2% sensitivity, 94.4% specificity, 0.03 negative, and 17.5 positive likelihood ratios. Conclusion: CAIT-THA is a validated tool that can be used in Thai younger adults. Clinicians and researchers can confidently use a score of ≤ 25 to determine the presence of CAI.IMPLICATIONS FOR REHABILITATION The Cumberland Ankle Instability Tool Thai version (CAIT-THA) questionnaire is available for Thai young adults. The CAIT-THA had high sensitivity, specificity, and positive and negative likelihood cut-off ratio scores for discrimination between chronic ankle instability (CAI) and non-CAI. The CAIT-THA questionnaire may be used in rehabilitation and research settings for the identification and management of CAI conditions.